Assessment of functional outcomes by Sheehan Disability Scale in patients with major depressive disorder treated with duloxetine versus selective serotonin reuptake inhibitors. (1st September 2015) - Sheehan, David V.; Mancini, Michele; Wang, Jianing; Berggren, Lovisa; Cao, Haijun; Dueñas, Héctor José; Yue, Li
Abstract : Objective: We compared functional impairment outcomes assessed with Sheehan Disability Scale (SDS) after treatment with duloxetine versus selective serotonin reuptake inhibitors (SSRIs) in patients with major depressive disorder. Methods: Data were pooled from four randomized studies comparing treatment with duloxetine and SSRIs (three double blind and one open label). Analysis of covariance, with last‐observation‐carried‐forward approach for missing data, explored treatment differences between duloxetine and SSRIs on SDS changes during 8 to 12 weeks of acute treatment for the intent‐to‐treat population. Logistic regression analysis examined the predictive capacity of baseline patient characteristics for remission in functional impairment (SDS total score ≤ 6 and SDS item scores ≤ 2) at endpoint. Results: Included were 2193 patients (duloxetine n  = 1029; SSRIs n  = 835; placebo n  = 329). Treatment with duloxetine and SSRIs resulted in significantly ( p  < 0.01) greater improvements in the SDS total score versus treatment with placebo. Higher SDS ( p  < 0.0001) or 17‐item Hamilton Depression Rating Scale baseline scores ( p  < 0.01) predicted lower probability of functional improvement after treatment with duloxetine or SSRIs. Female gender ( p  ≤ 0.05) predicted higher probability of functional improvement after treatment with duloxetine or SSRIs. Conclusions: Treatment with SSRIs and duloxetine improved functional impairment in patients with major depressive disorder. Higher SDS or 17‐item Hamilton Depression Rating Scale baseline scores predicted less probability of SDS improvement; female gender predicted better improvement in functional impairment at endpoint. © 2015 The Authors. Human Psychopharmacology: Clinical and Experimental published by John Wiley & Sons, Ltd.